Respostas

  • Usuário do Brainly
2014-05-28T15:19:01-03:00


substituição

y=5-10x                 17x+3y=-11               subs    y=5-10(2)

                                17x+3(5-10x)=-11                y=5-20

                                  17x+15-30x=-11                 y=-15         S= {(2,-15)}

                                   -13x=-26

                                     x=2


 adição  

(-3).(10x+y=5            -30x-3y=-15

                                   17x+3y=-11      cancela o y          -13x=-26        x=2

subs  em   10x+y=5

                   10(2)+y=5       20+y=5          y=2-20                 y=-15

                     

S={(2,-15)}


comparação

isolar y nas duas                y=5-10x   e   y=(-11-17x)/3

             comparo        5-10x=(-11-17x)/3

              mmc=3        15-30x=-11-17x

                                      -30x+17x=-11-15

                                               -13x=-26     x=2

subs 2 em  y=5-10x

                 y=5-10(2)

                 y=5-20       y=-15                   S={(2,-15)}

              

                                  

                                      -30x

1 5 1